ФОРМУВАННЯ ПАТРІОТИЗМУ У ДІТЕЙ СТАРШОГО ДОШКІЛЬНОГО ВІКУ ЗАСОБАМИ УСНОЇ НАРОДНОЇ ТВОРЧОСТІ - Динник, Яна Олександрівна (My University, 2023)
У роботі представлено результати дослідження проблеми формування патріотизму у дітей старшого дошкільного віку засобами усної народної творчості. Проаналізовано стан розробки проблеми формування патріотизму вітчизняними та зарубіжними науковцями; розкрито особливості формування патріотизму у дітей старшого дошкільного віку; визначено потенціал усної народної творчості у цьому процесі. Наведено результати дослідницької роботи з вивчення стану сформованості патріотичних почуттів у дітей старшого дошкільного віку та визначення педагогічних умов і методичних рекомендацій з формування патріотичних почуттів у дітей старшого дошкільного віку засобами усної народної творчості.
The paper presents the results of the study of the problem of the formation of patriotism in children of older preschool age by means of oral folk creativity. The state of development of the problem of formation of patriotism by domestic and foreign scientists is analyzed; the peculiarities of the formation of patriotism in older preschool children are revealed; the potential of oral folk creativity in this process is determined. The results of the research work on the study of the state of formation of patriotic feelings in older preschool children and the definition of pedagogical conditions and methodical recommendations for the formation of patriotic feelings in older preschool children by means of oral folk creativity are given. Keywords: patriotism, formation of patriotism, older preschool age, patriotic feelings, pedagogical conditions, optimization of the educational process, oral folk creativity.
Keywords: патріотизм; формування патріотизму; патріотичні почуття; старший дошкільний вік; усна народна творчість; педагогічні умови; оптимізація виховного процесу